Enhancing Students' Speaking Skills: The Impact of AI-Based Instructional Tasks in the Genre-Based Approach - Ahyarudin, Dahrul Ahmad; Jamilah, Jamilah (Formosa Journal of Sustainable Research, 2024)
This research explores the integration of AI-based Instructional Tasks (AI-IT) into the Genre-Based Approach (GBA) to improve vocational students' speaking skills. Conducted over two action research cycles with 35 hospitality management students in the 2023/2024 academic year, the study used interviews, observations, and document analysis, following Miles and Huberman’s framework. Member checks and triangulation ensured trustworthiness. Findings revealed that AI-IT significantly enhanced students’ vocabulary, pronunciation, and confidence, particularly in transactional language relevant to their field. The approach also increased classroom engagement and active participation. This study contributes to the evolving field of language teaching by demonstrating the potential of AI to support the development of speaking skills in vocational education, ultimately preparing students for real-world communication challenges in their careers